Analisis Dana Pihak Ketiga Dan Modal Terhadap Penyaluran Kredit PT. Bank Sulutgo - Jeifer Juandy Livingstone Rompas; Pingkan Aprilia Maramis (Jurnal Manajemen Bisnis Era Digital, 2024)
The purpose of this study is to analyze the effect of External Funds and Capital on credit distribution in PT. Bank Sulutgo . This research uses secondary data taken from Bank Sulutgo's annual report from 2012 – 2021. The analysis used is multiple regression analysis on the eviews application by taking data on third party funds, share capital and total credit distribution. Regression testing shows Y = 127 + 0.286 X1 + 7.490 X2. In the T test, it explains that the variable Third Party Fund has a significant influence on Credit Distribution and the results of the Capital variable have a significant influence on Credit Distribution, the amount of Third Party Funds and capital on Credit Distribution can be seen from the R-square of 0.98, meaning that X1 and X2 have a significant influence on Y by 98 percent and the rest by other factors.